Penerapan Design Thinking Eco-Boba dalam Pemanfaatan Limbah Cacahan Plastik dan Kemasan Paket E-commerce - Salma Amaliani Putri; Dewi Intan Sari; Khoirul Marzuki; Asep Taryana (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2022)
Indonesia became the second largest contributor of plastic waste in 2019 with 62% of it came from online shopping in e-commerce. The real anxiety is felt by the community so that it was necessary to implement a solution as an action to minimize the environmental impact of plastic waste, one of a way is by design thinking process. The first three stages of design thinking, namely empathize, define, and ideate became the crucial stages for fixationing an idea before they were tested. Through a descriptive analysis process from the results of interviews with 30 interviewees in depth, it was found that at the empathize stage, the ideas were explored using an empathy map. At the define stage, it was found that in the community there was still a lot of plastic waste with the type of plastic waste in the form of food, beverage or packaged plastic waste. Lastly, at the ideate stage, eco-boba was a solution resulting from design thinking in an effort to reduce plastic waste by using and processing plastic back into other products, namely pillow dolls filled with single-use plastic, both from flexible and rigid monomaterials.